Enhancement in Photocatalytic Efficiency of Commercial TiO2 Nanoparticles by Calcination: A Case of Doxycycline Removal - Nguyen Thi Cam Tien; Chau Hong Nhut; Vo Thi Thanh Thuy; Trinh Thi Bich Huyen; Lam Pham Thanh Hien; Nguyen Nhat Huy (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
In this study, the pure and calcined forms of Degussa TiO2 were applied for photocatalytic removal of doxycycline - a broad-spectrum tetracycline antibiotic. The calcination of TiO2 at 500 °C enhanced the photocatalytic efficiency of the TiO2 under optimal operational conditions of 5 ppm of doxycycline, 0.25 g/L of TiO2, pH 6.5, 120 min, and room temperature. In addition, the changes in morphology, crystal structure, and optical properties of the materials before and after calcination were observed by scanning electron microscopy, X-ray diffraction, and UV-Visible spectroscopy. The reaction kinetics of the doxycycline removal was also investigated based on the Langmuir-Hinshelwood model with a correlation coefficient R2 of >80%. Results showed that the photocatalytic ability of TiO2 is stable and enhanced after being calcined at a suitable temperature of 500 °C. This opens up the potential application of TiO2 in the treatment of emerging organic pollutants in water. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).